Differential Expression on a Daily Basis of Plastid Sigma Factor Genes from the Moss Physcomitrella patens. Regulatory Interactions among PpSig5, the Circadian Clock, and Blue Light Signaling Mediated by Cryptochromes - Ichikawa, Kazuhiro (Plant Physiol, 2004)
The nuclear-encoded plastid sigma factors are supposed to be a regulatory subunit of the multisubunit bacteria-type plastid RNA polymerase. We studied here whether or not three genes, PpSig1, PpSig2, and PpSig5 encoding plastid sigma factors, are controlled by the circadian clock and/or by blue light signaling in the moss Physcomitrella patens. Among the three PpSig genes, only PpSig5 was clearly controlled by the circadian clock. In contrast to the differential regulation on a daily timescale, a pulse of blue light induced the expression of all the three PpSig genes. This induction was significantly reduced in a knockout mutant that lacked the blue light photoreceptor cryptochromes PpCRY1a and PpCRY1b, indicating that PpCRY1a and/or PpCRY1b mediate the blue light signal that induces the expression of the PpSig genes. In a daily cycle of 12-h blue light/12-h dark, the timing of peak expression of PpSig5 and a chloroplast gene psbD, encoding the D2 subunit of photosystem II, advanced in the cryptochrome mutant relative to those in the wild type, suggesting the presence of regulatory interactions among the expression of PpSig5 and psbD, the circadian clock, and the blue light signaling mediated by the cryptochrome(s).